The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1002/1097-4679(198411)40:6<1288::aid-jclp2270400602>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

The schizophrenia spectrum: A study of the relationship among the Rorschach, MMPI, and visual backward masking

Abstract: Compared 20 Ss within the schizophrenia spectrum and 20 nonschizophrenia spectrum controls in terms of their MMPI and Rorschach performance. Ss also were studied in terms of their ability to identify a briefly exposed visual stimulus when it was followed by a noninformational mask stimulus and when it was not. Ss did not differ on the MMPI or on their ability to identify an unmasked target stimulus. They differed significantly in the number of deviant verbalizations, a special scoring category of the Rorschach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…among the normal, manic, and depressed control groups; however, the good and poor prognosis schizophrenic subjects had significantly longer critical ISIs than controls. In another study, Saccuzzo and Miller (1977) reported significantly longer critical ISIs in delusional schizophrenic patients than in a normal control group. Both of these studies were interpreted as supporting the notion that backward-masking performance is a direct reflection of information-processing speed.…”
Section: IImentioning
confidence: 89%
“…among the normal, manic, and depressed control groups; however, the good and poor prognosis schizophrenic subjects had significantly longer critical ISIs than controls. In another study, Saccuzzo and Miller (1977) reported significantly longer critical ISIs in delusional schizophrenic patients than in a normal control group. Both of these studies were interpreted as supporting the notion that backward-masking performance is a direct reflection of information-processing speed.…”
Section: IImentioning
confidence: 89%
“…Items are not erased when they are read out by attention into a more stable memory before the “mask arrives”. In schizophrenia patients, this read out process is slower (or otherwise disturbed) and, hence, performance is more strongly deteriorated in visual masking ( Braff, 1981 , Braff and Saccuzzo, 1981 , Braff and Saccuzzo, 1985 , Merritt and Balogh, 1984 , Patterson et al, 1986 , Saccuzzo and Miller, 1977 , Saccuzzo and Braff, 1981 , Saccuzzo and Braff, 1986 , Saccuzzo and Schubert, 1981 , Saccuzzo et al, 1974 , Saccuzzo et al, 1984 , Schwartz et al, 1983 ; for a review and criticism: Schuck and Lee, 1989 ; see also McClure, 2001 ). Research was concerned for about a decade with this hypothesis until the dual channel approach became the predominant view and research changed gears.…”
Section: Mechanisms and Modelsmentioning
confidence: 99%
“…Even the test's critics agree that some Rorschach scores are related to schizophrenia (Dawes, 1994;Wood, et al, 1996aWood, et al, , 1996b; but see Frank, 1990). As numerous studies have shown (e.g., Archer & Gordon, 1988;Hilsenroth, Fowler, & Padawer, 1998;Johnston & Holzman, 1979;Saccuzzo, Braff, Sprock, & Sudik, 1984;Wagner, 1998), psychotic patients who take the Rorschach often show slippage in the use of language ("deviant verbalizations") or report seeing things in the blots that other people cannot ("bad form"). Some Rorschach scores that are related to schizophrenia also appear to be related to bipolar disorder (Frank, 1990;Khadavi, Wetzler, & Wilson, 1997) and perhaps to schizotypal personality disorder as well (Hilsenroth et al, 1998).…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…Because the symptoms of schizophrenia tend to be striking and serious, there is usually little point in administering the Rorschach to confirm a diagnosis established by clinical interview or collateral information. Furthermore, if testing is deemed necessary, the Minnesota Multiphasic Personality Inventory (MMPI) is considerably less expensive and seems to be equally or more valid for the purpose than the Rorschach (Archer & Gordon, 1988; but see Saccuzzo et al, 1984). For example, although the CS Schizophrenia Index (SCZI ) (Exner, 1986a; is related to schizophrenia, no published studies have shown that it can add significant incremental validity for diagnoses of the disorder, beyond what can be obtained from an interview and MMPI scores.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%